Fatal laryngeal papillomatosis in an infant. - Jerkovic Gulin, S.; Habek, D.; Hrgovic, Z.; Gulin, D.; Cerkez Habek, J. (European Journal of Pediatric Dermatology, 2019)
We describe the case of an infant who was born to a mother with genital warts at the time of the birth. The patient presented in the first month of life a severe recurrent laryngeal papillomatosis, responsible for multiple operations, tracheotomy, rapid spread and death at the age of 3 and a half months.